Analysis of The Implementation of Tax Planning in Efforts to Save Corporate Income Tax Expense in PT GMT year 2017 - Ening Budi Herwati; Ratih Kumala (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
Tax planning is the first step in tax management. Tax management is a means to meet tax obligations well, but the amount of tax paid can be reduced to a minimum to obtain the expected profit. This research aims to analyze the implementation of tax planning conducted by PT GMT. The research approach used by the authors is descriptive qualitative. This research result is expected to provide information and suggestion for PT GMT that company could conduct tax planning as tax payment efficiency effort to gain maximum profit, but remain within tax regulation. Summary of this research revealed that tax planning implementation carried out by PT GMT could efficient payable tax expense. And company could save amounted to Rp.18.231.325,- from previous total payable tax.